2011
DOI: 10.1002/em.20658
|View full text |Cite
|
Sign up to set email alerts
|

Measures of genotoxicity in Gulf war I veterans exposed to depleted uranium

Abstract: Exposure to depleted uranium (DU), an alpha-emitting heavy metal, has prompted the inclusion of markers of genotoxicity in the long-term medical surveillance of a cohort of DU-exposed Gulf War veterans followed since 1994. Using urine U (uU) concentration as the measure of U body burden, the cohort has been stratified into low-u (<0.10 μg U/g creatinine) and high-u groups (≥ 0.10 μg U/g creatinine). Surveillance outcomes for this cohort have historically included markers of mutagenicity and clastogenicity, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…An analysis of Gulf War I veterans exposed to alpha particle emitting depleted uranium has also identified a significant 50% increase in HPRT mutant frequency compared to a low exposure group [106] and a number of other studies have also observed the mutagenic and clastogenic potential of depleted uranium exposure [107,108]. …”
Section: Genetic Effectsmentioning
confidence: 99%
“…An analysis of Gulf War I veterans exposed to alpha particle emitting depleted uranium has also identified a significant 50% increase in HPRT mutant frequency compared to a low exposure group [106] and a number of other studies have also observed the mutagenic and clastogenic potential of depleted uranium exposure [107,108]. …”
Section: Genetic Effectsmentioning
confidence: 99%
“…Soluble uranyl ion has been found to be clastogenic, transforming, and aneugenic in cell culture [3032]. Mutations at the hprt locus have been reported for soluble uranyl ion in Chinese Hamster Ovary (CHO) and V79 cells [8, 33], as well as in peripheral T-cells of gulf war veterans exposed to DU containing shrapnel [34]. Characterization of the mutagenic spectrum in CHO EM9 cells exposed to uranyl acetate (UA) showed more small multiexon 1–22 bp deletions and 1–2 bp insertions than were observed in either spontaneously-generated or H 2 O 2 -induced hprt mutants [35].…”
Section: Introductionmentioning
confidence: 99%
“…For this day 1, and on the following days 3, 6, 8, and 10, the cells were counted and the GPI-a cloning assay was performed as described [McDiarmid et al 2011]. On each of the five days, 10 × 10 6 cells at 0.5 × 10 6 cells/ml were maintained in RPMI-10% CBS for the next day of analysis.…”
Section: Methodsmentioning
confidence: 99%